A population-based study of neonatal air transport in the Arctic region of Norway from 1994 to 2023 - Trulsen, Lene Nymo; Hansen, Lisa Gullhav; Songstad, Nils Thomas; Lang, Astri; Klingenberg, Claus (Frontiers in Pediatrics, 2025)
Background and aimsRegionalized centralization of moderate and high-risk pregnancies is essential, but a well-organized postnatal transport service is equally important. This study evaluates the overall activity and clinical outcomes of the neonatal air transport team (NATT) at the University Hospital of North Norway (UNN) in Tromsø, covering a large catchment area in the Arctic region of Norway.MethodsMedical data from all neonatal air transports between the years 1994–2023 were recorded prospectively. Body temperature, blood glucose and blood gas within 3–6 h after arrival at UNN were assessed from medical files retrospectively. To assess temporal changes, we compared data between 1994 and 2008 (Period 1) and 2009–2023 (Period 2).ResultsA total of 882 acute transports were included. Of these, 655 (74.3%) were referrals to the tertiary neonatal unit at UNN and 227 (25.7%) transfers to national surgical centers. Most transports (61.5%) were by fixed wing aircrafts. The proportion of infants transported due to congenital heart defects (CHD), prematurity and asphyxia was lower in Period 2. When comparing Period 1 and 2, upon arrival we found similar rates of hypothermia (9.8% vs. 6.7%, p = 0.17) and hypercapnia (17.3% vs. 15.3%, p = 0.55), but decreasing rates of hypocapnia (6.7% vs. 2.5%, p = 0.014) and hypoglycemia (10.8% vs. 2.3%, p = 0.001). There were low rates of outborn very low birth weight (VLBW) infants (<1,500 g) in both periods; 4.3% and 3.1%. However, severe IVH was observed in 6/29 (20.7%) outborn VLBW-infants vs. only 21/356 (5.9%) inborn VLBW-infants in the last 15-year period.ConclusionDecreasing rates of transport due to prematurity and CHDs is probably secondary to improved perinatal care. Rates of hypoglycemia and hypocapnia improved in the second 15-year period, but further focus on improvements in both temperature and CO2 control is warranted. Acute transport of VLBW-infants is associated with a markedly increased risk of severe IVH. In-utero transfer of women with threatened preterm birth to a tertiary perinatal center is therefore paramount.